Efeito da substituição tributária sobre a arrecadação do ICMS nos setores industrial, varejista e atacadista: um estudo de caso para o decreto nº 31.270/2013 no Ceará - Teixeira, Inês Cristina (2017)
This paper proposes to verify if tax collection of retail, wholesale and industrial sectors was positively affected by Decree 31.270/2013, -, which regulated Law No. 14.237 / 2008, had as objectives the need to establish a system of operational and simplified taxation for taxpayers, in the State of Ceará. To do this, was performed structural breaks tests performed based on the endogenous approach of Bai and Perron on the collection of ICMS in the industrial, retail and wholesale segments for the period from January 2005 to August 2017. The results suggest that the tax replacement caused a structural break in the temporal dynamics of the series of sectoral ICMS. In addition, the estimation of multiple linear regression models reported that the implementation of the change in the tax collection system caused an anticipation of ICMS revenues from stored inventories, with a subsequent reduction in the collection volume from 2015, when the stocks were zeroed.